Conflict as a manifestation of social relations (Actual Problems of Psychology in Educational Institutions, 2022)
It has been generalized the theoretical researches which is accumulated in the field of conflict psychology. It has been considered the ways to overcome conflict, the concept of conflict in different variations. The main attention in the work has been devoted to the psychological researches of the individual’s behavior in a conflict situation and presented the analysis of the results.